2022
DOI: 10.1177/09612033221122163
|View full text |Cite
|
Sign up to set email alerts
|

Factors mediating cancer risk in systemic lupus erythematosus

Abstract: Patients with systemic lupus erythematosus (SLE) are at an elevated risk for certain cancers compared to the population at large. Cancers seen at higher rates in the SLE population include hematologic malignancies, such as non-Hodgkin lymphoma, and cancers of the lung and thyroid. SLE patients also have a decreased risk for certain malignancies, such as breast cancer, melanoma, and prostate cancer. We review the literature on risk factors for malignancy in patients with SLE and discuss the exogenous and innate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 109 publications
0
5
0
Order By: Relevance
“…The idea that preclinical autoimmunity could play a functional role against cancer seems somewhat provocative, but the growing use of immunotherapies proves the efficacy of harnessing the immune system to control established tumors. A growing body of research also suggests potential protective associations of RA and SLE with risk of breast cancer, though the mechanisms are unknown, and the evidence is inconsistent [38][39][40]. The current study design and relatively small sample size precludes a definitive evaluation of ANA and autoimmune diseases in relation to breast cancer, though we note a lower frequency of self-reported lupus in cases compared to controls, regardless of ANA status (Table 1).…”
Section: Discussionmentioning
confidence: 70%
“…The idea that preclinical autoimmunity could play a functional role against cancer seems somewhat provocative, but the growing use of immunotherapies proves the efficacy of harnessing the immune system to control established tumors. A growing body of research also suggests potential protective associations of RA and SLE with risk of breast cancer, though the mechanisms are unknown, and the evidence is inconsistent [38][39][40]. The current study design and relatively small sample size precludes a definitive evaluation of ANA and autoimmune diseases in relation to breast cancer, though we note a lower frequency of self-reported lupus in cases compared to controls, regardless of ANA status (Table 1).…”
Section: Discussionmentioning
confidence: 70%
“…TP53 protein is a transcription factor that inhibits tumor formation and plays an important biological role in promoting DNA damage repair, inducing apoptosis, senescence and cell cycle arrest [33] . Studies have found that SLE patients have a significantly higher risk of certain cancers than the general population, most commonly haematological malignancies, lung cancer and thyroid cancer [34] . AKT1 is involved in many BPs, including metabolism, proliferation, cell growth and angiogenesis.…”
Section: Resultsmentioning
confidence: 99%
“…Mosca [35] University of Pisa Italy 3 134 67 According to the results of journal analysis, Arthritis Research and Therapy, Frontiers in Endocrinology, Autoimmunity Reviews, and Lupus, were the highest ranked journals in publishing related articles regarding this topic, respectively. [25][26][27][28] Considering that 8 of the top 10 most productive journals in this field of research were situated in Q1, it is evident that research in this area has attained a relatively advanced stage.…”
Section: Discussionmentioning
confidence: 99%